TOXIC POSITIVITY: THE DYNAMICS OF INTERPERSONAL COMMUNICATION ON MEDIA X IN THE ERA OF CANCEL CULTURE - Harahap, Muhammad Rizkie Habibie; Yusniah, Yusniah (Journal Analytica Islamica, 2025)
This study aims to examine the dynamics of interpersonal communication on the Media X platform within the context of the phenomena of toxic positivity and cancel culture. These two phenomena represent a paradox of digital culture: on one hand, there is an incessant push for maintaining positivity, often dismissing the validity of negative emotions; on the other hand, there is the rise of collective cancellation practices that can create intense social pressure. This research employs a qualitative approach using a netnographic strategy, supported by content analysis of user-generated posts and interactions. Data were collected through digital observation, documentation of online conversations, and the use of Brand24 as a social media analytics tool. The findings reveal that toxic positivity is frequently normalised through phrases such as "keep your spirits up," which appear across various emotional contexts but tend to suppress more honest and complex emotional expressions. Simultaneously, cancel culture has evolved as a mechanism of collective moral control, often enacted without clarification processes or opportunities for restitution. These phenomena shape a communication landscape characterised not only by rapid and emotional exchanges but also by intense social and symbolic pressures. This study underscores the necessity for critical awareness and ethical communication practices within a digital ecosystem marked by polarisation. In conclusion, online spaces require a more reflective, empathetic, and inclusive communication approach to ensure that digital practices support emotional well-being and foster humane dialogue, rather than merely reinforcing image management.